Misinformation, knowledge and COVID-19 vaccine acceptance: a cross-sectional study among health care workers and the general population in Kampala, Uganda - Atuheirwe, Maxine; Otim, Richard; Male, Keneth Junior; Ahimbisibwe, Stella; Sackey, Joachim Dzidzor; Sande, Obondo James (BMC Public Health, 2024)
COVID-19 has greatly affected communities worldwide, more so in low- and middle-income countries. To successfully resolve the COVID-19 pandemic, vaccination coverage of more than 80% is required. However, misinformation has affected this by increasing COVID-19 vaccine hesitancy. Limited studies have assessed the effect of COVID-19 misinformation on vaccine acceptance, especially in Africa. This study assessed people’s knowledge of the COVID-19 vaccine and the effect of misinformation on vaccine uptake among healthcare workers (HCWs) versus the general population in Uganda. Methods This was a cross-sectional quantitative study conducted from January 2022 to June 2022, and involved healthcare workers (HCWs) and the general population of Kampala, Uganda. A structured questionnaire was used to collect data. We recruited 564 study participants, including 311 healthcare workers (HCWs) and 253 from the general population. Data were analyzed using frequency distributions and Chi-square tests. SPSS version 22.0 was used to conduct all study analyses. Results This study revealed that the proportion of vaccinated HCWs (77.4%) was significantly higher than that of the vaccinated general population (64.4%, p = 0.010). Nearly all study participants were aware of COVID-19 vaccines (96.7%). The research revealed that a large proportion of the participants (89.7%) encountered rumors regarding unverified adverse effects of the COVID-19 vaccine. This information significantly contributed to vaccine hesitancy, with 81.1% expressing reluctance to receive the vaccine, and 55% stating their unwillingness to get vaccinated. Misinformation affected people’s vaccine acceptance, affecting their willingness to receive vaccines if unvaccinated and potentially influencing their receptiveness to future vaccines or boosters if already vaccinated. Conclusions The study showed a negative impact of misinformation on vaccine uptake and could be the most significant contributor to vaccine hesitancy in future vaccine programs.
Keywords: COVID-19; COVID-19 vaccine; Misinformation; Health care workers; General population